Energy and reserve co-optimization within the Short Term Hydrothermal Scheduling under uncertainty: A proposed model and decomposition strategy - Lopez Salgado, Carlos Josue (2016)
Procurement of spare capacity is an essential mechanism in electric power systems. Through it the system is able to endure the disturbances induced by different sources of uncertainty, which also impact the system's operational cost. This paper introduces an optimization model for the Short Term Hydrothermal Scheduling that performs a co-optimization of energy and reserves for tertiary regulation, considering hydrology uncertainty and forced outages of generation units and transmission lines. The formulation presented is extended to consider intermittent stochastic generation from wind farms or hydro plants without storage capability. This work also proposes a decomposition scheme to deal with the resulting stochastic and large scale optimization problem. The proposed strategy relies on a coordinated application of two instances of the Bender's decomposition principle. By means of two study cases it will be demonstrated the effectiveness of the proposed model and the performance of the methodology.